RANCANGAN DAN IMPLEMENTASI SISTEM MANAJEMEN ENERGI DAN AUDIT ENERGI BERBASIS ISO:50001 DI KAMPUS UNIVERSITAS ISLAM KALIMANTAN - Ditza Pasca Irwangsa; Jaka Windarta; Susatyo Handoko (Scientific Journal of Mechanical Engineering Kinematika, 2023)
The use of electricity without following standards, safety, and regulations can lead to inefficiency and ongoing crises. This study aims to analyze efficiency, design strategies, and implement an Energy Management System (EMS) based on ISO 50001 at the Islamic University of Kalimantan. The methods involve literature review, observation, surveys, and primary and secondary data collection. An energy audit in three buildings on the UNISKA campus revealed an energy consumption intensity (IKE) of 16.16 kWh/m2/month, which is inefficient according to the 2012 DEPDIKNAS standards. The Gap-Analyst method was used to calculate the difference between actual and desired IKE, resulting in a difference value of 4.52 kWh/m2. With IKE savings of 11.64 kWh/m2/month, the total saved cost amounts to Rp. 81,839,250, achieving a 27.93% reduction. UNISKA management is expected to implement recommendations and the ISO 50001-based Energy Management System for energy efficiency.